Hepatoprotective Action of Terminalia Chebula, Terminalia Billerica, and Emblica Officinalis (Triphala): A Review - Naqvi, Rehan; Mehdi, Asghar; Das, Geetha Kumari (International Journal of Integrative Sciences, 2024)
Liver afflictions are an important global well-being burden, making the study of everyday remedies such as Terminalia chebula, Terminalia bellerica, and Emblica officinalis (Triphala) important for their hepatoprotective effects. Terminalia chebula, Terminalia Billerica, and Emblica officinalis are famous for their different bioactive compounds, containing polyphenols, flavonoids, tannins, and vitamins, which award antioxidant, antagonistic-instigative, and hepatoprotective characteristics.Several in vitro and in vivo studies have manifested the capability. Triphala, an established Ayurvedic formulation including equal parts of Terminalia chebula, Terminalia bellerica, and Emblica officinalis, exhibits cooperative hepatoprotective belongings distinguished from individual components that are necessary for the complete conduct of allure constituents. Clinical studies judging Triphala have stated promising results in improving liver function stones and reducing manifestations of liver ailments. In conclusion, Terminalia chebula, Terminalia bellerica, and Emblica officinalis, both separately and as Triphala, hold huge potential as open hepatoprotective powers. Further research, including dispassionate problems and mechanistic studies, is authorized to obtain across their efficacy, safety, and latent microscopic mechanisms, concreting the habit for their unification into prevailing medicine for liver health management and affliction administration